'Life does not make it easy to breast-feed': using the socio-ecological framework to determine social breast-feeding obstacles in a low-income population in Tijuana, Mexico. Issue 18 (5th March 2015) - Bueno-Gutierrez, Diana; Chantry, Caroline
Abstract: Objective: Breast-feeding rates reflect sociodemographic discrepancies. In Mexico, exclusive breast-feeding under 6 months of age has deteriorated among the poor, rural and indigenous populations from 1999 to 2012. Our objective of the present study was to identify the main social obstacles to breast-feeding in a low-income population in Tijuana, Mexico. Design: Qualitative study using a socio-ecological framework for data collection. Setting: Low-income communities in Tijuana, Mexico. Subjects: Mothers ( n 66), fathers ( n 11), grandparents ( n 27) and key informants ( n 25). Results: One hundred and twenty-nine individuals participated in the study: six focus groups ( n 53) and fifty-one interviews among mothers, fathers and grandparents; and twenty-five interviews among key informants. Seven social themes were identified: (i) embarrassment to breast-feed in public; (ii) migrant experience; (iii) women's role in society; (iv) association of formula with higher social status; (v) marketing by the infant food industry; (vi) perception of a non-breast-feeding culture; and (vii) lack of breast-feeding social programmes. Conclusions: Socio-structural factors influence infant feeding practices in low-income communities in Tijuana. We hypothesize that messages emphasizing Mexican traditions along with modern healthy practices could help to re-establish and normalize a breast-feeding culture in this population. The target audience for these messages should not be limited to mothers but also include family, health-care providers, the work environment and society as a whole.